Designing A Mobile-Based Attendance Application Using Location-Based Service for Activities Mosque - Atika Dewi Zulaikha; Afwan Anggara (Universitas Negeri Semarang, 2026)
Purpose: The purpose of this study is to design a mobile-based attendance application that uses Location-Based Services to support community-based religious institutions, namely mosques, which are simple to understand for all age groups, make it easier for participants to take attendance, and make it easier for administrators to manage participant data, schedules, and attendance. Methods: Interviews and direct observations were conducted to identify problems and determine the new system required. This system utilizes the concept of geolocation by utilizing GPS and geofencing for location validation, which is described using UML and implemented in programming. The completed system was tested through blackbox testing for its features and GPS accuracy testing to determine the stability of the location tracking system. Result: Blackbox testing results show that the functions integrated into the attendance application can run 100% as expected. The GPS accuracy system performance test results obtained are sufficient for semi-outdoor and outdoor spaces with 100% valid results. Novelty: The uniqueness of this research lies in its contribution to community-based religious institutions, namely mosques, in digital attendance recording, as well as providing GPS accuracy evaluation results provided by the system to determine the most appropriate radius range. Further developments that can be made to the system include improving security procedures, as this application directly accesses the user's location, making improvements to the security system and fake location detection very important for attendance applications.